Structural-functional model of professionally-directed education - Koroleva V. V. (Interactive science, 2016)
in this paper reviewed the technology professionally-directed education in the new educational paradigm. Attempted to construct a model of the educational process. A scheme of notation structural and functional analysis.
Keywords: Model; построение модели; структурно-функциональный анализ; профессионально-направленное образование; structural and functional analysis; professional-directed education